ROLE OF PHYSIOTHERAPY IN PREVENTION AND TREATMENT OF EXERCISE INDUCED BRONCHOSPASM AND BRONCHIAL ASTHMA - Dr. Shishir Nigam, Dr. Shobhit Saxena, Dr. Jitender Munjal, Dr. Ashish M Agrawal, Dr. Devesh Seth , Dr. Ankita Sharma (South Eastern European Journal of Public Health, 2025)
Exercise-induced bronchospasm and bronchial asthma are widespread respiratory disorders that can significantly limit physical activity and reduce quality of life. Physiotherapy plays an essential role in the prevention, management, and treatment of these conditions by improving airway function, boosting respiratory efficiency, and enhancing exercise capacity. This review examines the contribution of physiotherapy in managing exercise-induced bronchospasm and bronchial asthma through a combination of interventions such as breathing exercises, airway clearance techniques, postural drainage, and physical conditioning. By focusing on strategies that enhance lung function and decrease bronchial hyperresponsiveness, physiotherapists enable individuals with asthma or exercise-induced bronchospasm to engage in physical activity in a safe and effective manner. The review also highlights the scientific evidence supporting physiotherapy interventions and offers recommendations for incorporating these approaches into asthma management strategies to improve both short-term results and long-term respiratory health.